Ser mãe eu sei, o que agora falta é social : sobre o processo de constituição da identidade profissional no Acolhimento Institucional de Crianças - Lima, Aline Ottoni Moura Nunes de (2009)
This work aimed to comprehend how social mothers give meaning to their daily life in an Institutional Shelter and to analyze their inter-relations with the making up of Professional identity. We were guided by a Historical-material dialect of man and world and the expression of this in Psychology which considers the making up of a person as a human being as a material and historical character and is made up in and from the established relations between I and the other throughout ontogenesis. We also assume that the process of building professional identity of the Social Mothers surges from a network of personal and social articulated interactions which make multiple meanings possible in a dialectic process. We then performed a qualitive research in which we interviewed two professionals (Social Mothers), responsible for the direct care of children in temporary and exceptional shelter. Interviews were taped individually and completely transcribed. From there, we defined, through an adaption of idea association maps proposed by Spink e Lima (2000), four general categories: 1) family history; 2) work at the shelter; 3) the social mothers and the children; 4) the social mothers and other actors of the guarantee of rights system. The basic fundamental that oriented our analysis was the interpretive character of knowledge, highlighted by Gonzáles-Rey (2002), which consists in a process of giving meaning to the expressions of the participants in a way of integrating them so as they can make sense to the group of researchers. Our interviews produced a context of review and emergence of meanings upon the activity Social Mother made from phylogenetic development as well as ontogentic development. Family histories were highlighted especially those that were connected to meanings of child, family and Institutional Shelter. The question about what it is to be a Social Mother led to talk of the professionals to a movement of fusion (action repetition) and differentiation (creation) in the construction of meanings on social mothering played by them. We emphasize however that professional identity is not a data or a fragmented product, an isolated character lived by the person in his/her life, but a whole in composition involving multiple social roles inserted in historical and cultural context.